2009
DOI: 10.1111/j.1944-9720.2009.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

If You Don't Know Where You're Going, You'll Wind up Somewhere Else: The Case of “Foreign Language Learning Disability”

Abstract: Despite the lack of empirical evidence, the term foreign language learning disability (FLLD) has become popular in the learning disabilities (LD) and foreign language literature. I contend that there is not a unique “disability” for foreign language learning and suggest instead that foreign language skills run along a continuum of very strong to very weak foreign language learners. To support my positions, I review problems with the definition and diagnostic criteria for LD. Then, I cite problems with the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 89 publications
0
23
0
7
Order By: Relevance
“…Although contemporary, standards-based, proficiency-oriented instruction emphasizes very different goals, these, among other misunderstandings of language acquisition, have been found to hinder the development of inclusive foreign language learning classrooms (Arries, 1999) while perpetuating beliefs among learners, counselors, administrators, parents, and even some language educators that exemptions are necessary. In fact, some educators and researchers are still attempting to classify students as foreign language learning disabled, a classification that may, unfortunately, focus on exempting students rather than on adjusting curricular and instructional practices to meet their needs (Sparks, 2006(Sparks, , 2009.…”
Section: Policies and Practices Of Language Exemptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although contemporary, standards-based, proficiency-oriented instruction emphasizes very different goals, these, among other misunderstandings of language acquisition, have been found to hinder the development of inclusive foreign language learning classrooms (Arries, 1999) while perpetuating beliefs among learners, counselors, administrators, parents, and even some language educators that exemptions are necessary. In fact, some educators and researchers are still attempting to classify students as foreign language learning disabled, a classification that may, unfortunately, focus on exempting students rather than on adjusting curricular and instructional practices to meet their needs (Sparks, 2006(Sparks, , 2009.…”
Section: Policies and Practices Of Language Exemptionsmentioning
confidence: 99%
“…This means that many students with disabilities do not benefit from this educational opportunity, which would seem contradictory to inclusive beliefs. Sparks ( ) called for advocates for students with disabilities to be “consistent with their inclusion philosophy and insist that students classified as [learning disabled] be enrolled in foreign language courses and provided with appropriate teaching methods and instruction accommodations so that they can be successful in these classes” (p. 18).…”
mentioning
confidence: 99%
“…When discussing all of the scenarios, special emphasis was placed on the clarification of misconceptions regarding disabilities, ranging from the disabilities or conditions for which students could receive accommodations to what constitutes a disability and whether there was a connection between specific learning disabilities and learning foreign languages (Sparks, , ). In the third session, participants asked questions to confirm and clarify their understanding and general concepts were reviewed as a group.…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies have found that faculty did not participate in training opportunities due to time constraints (Rao & Gartin, ; Salzberg et al, ; Scott & Gregg, ). Studies have also found that some instructors held negative preconceptions regarding accommodations because they feared that academic integrity would be compromised and had difficulty conceptualizing both the idea of fairness and approaches for implementing fair practices (Bourke, Strehorn, & Silver, ; Cook et al, ; Houck et al, ; Jensen, McCrary, Krampe, & Cooper, ; Matthews, Anderson, & Skolnick, ; Nelson, Dodd, & Smith, ; Sparks, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation